(3GdWQR GdCSei Ydi cfR GdCSeGAs - (3eYjf GdOjf YHO GdeYjf Hf CMeO GdTgjQ HGHf GdHWGd GdHdNis; (3bWH GdOjf eMeO Hf YdGA GdOjf CMeO Hf TeS GdOjf GdMfajs ((3Ydi Hf eMeO GdedGM s)
(3ChdgG (B:s
(3HfgGjI CNP fjGWi GdPcQ CHJOF hXaQfi HcfR GdCSeGA ai Yde GdeYei JCdja bWH GdOjf Gdeci GdMfai fRgJ NGWQi ai GdQJhY ai QjGV CRGgQg heJYJ WQai HGdJCed ai aQGFO LhGgQg s
(3BNQgG (B:s
(3CQOJ HKdK GdNejS GdNGA hgj HSJeGFg hKdKgG GdQGA hcGf SdN GdeMQe YTjI GdNejS GdeHGQc NJGeg ai SfI KdGKI hJSYjf hJSYeGFI Je HMeO Gddg hYhfg hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1513s
Keywords: (3GdCOHs